Firm-specific, and institutional determinants of corporate investments in Nigeria - Folorunsho M. Ajide (Future Business Journal, 2017)
We examined the effect of institutional quality and firm-specific factors on corporate investment in Nigeria using fifty-four (54) quoted non-financial firms within the period of 2002-2012. We applied dynamic panel estimator proposed by Arellano-Bond (1991). The results showed that regulatory quality, corruption, political stability and control of corruption have insignificant effect in determining corporate investments in Nigeria. Our results also confirmed that firms' firm-specific factors influenced corporate investment in Nigeria. While firms' cash flow displayed positive and significant effect on investment other factors had negative effects on investment.Our results showed that investment is constrained to internally generated fund, despite the existence of capital market. In addition, the spillover effect of tightening monetary policy during the period of study had increased the cost of borrowing thereby having a negative effect on investment in the real sector. We recommended that when the monetary authorities are focusing on inflation targeting, they should also not lose sight of its impact on corporate investment and other productivity growth of firms; which is the source of long term sustainable growth and development of economies.
Keywords: 650; Firm-specific; GMM; Institution; Investment; Nigeria